Management of Posyandu Services for the Elderly Regarding Activeness in Conducting Visits - Sajidin, Muhammad; Andriyanto, Arief (Jurnal Kesehatan Pasak Bumi Kalimantan, 2026)
Elderly Integrated Health Service Posts (Posyandu Lansia) are community-based health services that play an important role in improving the health status and quality of life of older adults. However, the activeness of older adults in attending Posyandu activities remains suboptimal and may be influenced by the quality of service management. Effective service management is expected to enhance comfort, satisfaction, and participation among older adults in utilizing Posyandu services regularly. This study aimed to analyze the relationship between Posyandu service management and the activeness of older adults in attending Posyandu visits. This study employed a correlational analytic design with a cross-sectional approach. A total of 103 older adults were recruited using purposive sampling. Data were collected using questionnaires assessing Posyandu service management and the activeness of Posyandu visits. Data were analyzed using the Spearman correlation test with a significance level of 0.05. The results showed that most respondents perceived Posyandu service management as good and demonstrated a high level of attendance. Correlation analysis revealed a significant relationship between Posyandu service management and the activeness of older adults in attending Posyandu visits (p < 0.05), indicating that better service management was associated with higher participation in Posyandu activities. Optimal management of Posyandu services can increase regular attendance among older adults and support continuous health monitoring. Healthcare professionals and community health volunteers should strengthen service quality, improve service accessibility and comfort, and involve family members to encourage active participation in Posyandu programs